POST-ADOPTION BEHAVIOR MODEL DEVELOPMENT OF MOBILE PAYMENT SERVICES AS A PAYMENT TRANSACTION MODE AT CASHIER/STORE - Akbar Maharoesman, Rizky
The rapid development of information technology and the fast-paced lifestyle are driving the growth of FinTech as a solution to ease the payment transaction process. Currently, mobile payment, one of FinTech type, is becoming a growth market in Indonesia. However, a survey by Jakpat showed that only 26.5% of respondents plan to continue using the mobile payment service they currently use. This needs to be a concern for mobile payment service providers because retaining users is vital for business success. The research related to user retention of Information System / Information Technology (IS / IT) is the post-adoption behavior of information system users. Expectation-Confirmation Model (ECM), Information Systems Success Model (ISSM), and Technology Acceptance Model (TAM) are approaches that are often use in post-adoption behavior research. The proposed model in this research is use the ECM approach with the addition of several variables such as word of mouth, information quality, system quality, mobile service quality, and habit. This study uses 459 user data of mobile payment service collected through an online questionnaire survey. The data then processed using the PLS-SEM method. The results showed that information quality and service quality proved to have a direct effect on confirmation and satisfaction, while mobile service quality have a direct effect on the confirmation but not shown to have a direct effect on satisfaction. Compared with other aspects of quality, information quality is the strongest predictor for confirmation while system quality is the strongest predictor for satisfaction. The results in this study also indicate that satisfaction, perceived usefulness, and habit have a direct effect on continuance intention while satisfaction, perceived usefulness, and continuance intention have a direct effect on word of mouth. Also, through the results of this, it is known that study habit is the strongest predictor of continuance intention, and continuance intention is the strongest predictor of word of mouth.